An Authentic Project-Based Assessment Model for Vocational High School Students Grade X - Sastrikirana, Anastasia (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2015)
The aim of Indonesia National Education is to bring its people and country towards betterdevelopment of skills and characters or attitude in order to be democratic and responsiblecitizens. A curriculum needs to be created in order to support the achievement of this goal.The current curriculum 2013, has tried to emphasize on knowledge, skills and attitude all ofwhich are in line with the goal of Indonesia National Education. It emphasizes on three typesof learning namely project-based, problem-based, and discovery learning in order to promotemore skilful people. Yet, it is problematic in some ways for it does not provide enough timeallocation for knowledge and skill development. English is now taught in one meeting only ina week. Also, the problem lies in the assessment. It separates the assessment of knowledge,skills, and attitude. It seems to forget that in those types of learning, students have to integratethose aspects in order to accomplish a projector to solve a problem. The partial assessmentmakes those types of learning impossible. Therefore, an alternative authentic and holisticassessment for a year project for vocational high school students is developed to improvestudents‟ progress as a whole.Keywords: project-based learning, authentic assessment, vocational high school